The effects of immigration and integration on European budgetary trade-offs. Issue 6 (17th June 2017) - Lipsmeyer, Christine S.; Philips, Andrew Q.; Whitten, Guy D.
ABSTRACT: What affects government policy-making continues to be an important question for researchers interested in political competition and policy priorities. In this contribution, we bring together a theoretical framework that focuses on the influence of globalizing forces on government policy decisions with a methodological emphasis on explaining dynamic budgetary trade-offs. While comparative public policy and budgetary scholars typically have focused on entire budgets or amounts spent on specific policies, we look at the political priorities embedded in budgets by modeling the budget as a pie. Then, we theorize about how governments respond to external shocks by altering the allocations to the various policy areas. Using this approach, we find that governments of different ideological types react to external shocks by altering their different policy priorities.